Optimization of maritime operations in Arctic. Rating of improvement of weather routing/decision support systems for maritime operations in the Arctic region - Johansen, Kåre (Universitetet i Tromsø, 2013)
Abstract The decreased ice extent caused by increased air and sea temperatures has led to a growing interest in the Arctic waters. There are different maritime industries that have plans to expand northwards for various reasons. First of all there are different developments in oil and gas industry in Barents, Kara, Greenland, Arctic sea around the coast of Canada and Alaska. New ship trading routes like The Northern sea route and The North west passage. Fishing industry are moving north along with fish stocks. A growing interest from cruise and tourism industry seems also to be an increasing trend. Therefore, reliable ship routing/decision support systems need to be evaluated, developed, improved, implanted and made available to maritime industry in Arctic. To make a reliable ship routing/decision support systems it is important to take into consideration experiences from accidents that have happened in the Arctic areas. These accidents can help us to provide a clear view on what type of information, data, communication, infrastructure and other resources that needs to be developed. The main lessons to be learned from former accident are that to be able to conduct more efficient and safer maritime operations, more and better information needs to be available. This must be in terms of supporting decision systems based on different remote sensing information. Nothing of this is possible without a maritime communication infrastructure with sufficient bandwidth and integrity. The main approach to the task was to come up with a proposal to an ice information algorithm based on appropriate remote sensed ice information. The proposed algorithm was meant to be a contribution or an improvement to an existing ship routing/decision support system. In addition to this algorithm proposal there will be taken a comparison between the weather input from an existing ship routing/decision support system and weather information from Norwegian Meteorological Institute (NMI). There were numerous suitable routing/decision systems, ...